Static Design for Laterally Loaded Rigid Monopiles in Cohesive Soil - Ruping Luo; Mingluqiu Hu; Min Yang; Weichao Li; Anhui Wang (Journal of Marine Science and Engineering, 2023)
Rigid monopiles with small slenderness ratios (i.e., ratio of monopile embedded length to outer diameter) are widely used as foundations to resist lateral load and moment transferred from superstructures, e.g., large diameter steel pipes used by offshore wind turbines and piers in electric utility industry or sound barriers. A design model for laterally loaded rigid monopiles in cohesive soil is presented in this paper. The proposed design model assumes a constant depth of rotation point as well as a trilinear distribution model of soil lateral reaction along the embedded length of the monopile, and introduces a mobilization coefficient of soil reaction to quantify the magnitude of soil reaction mobilized under a certain load applied at the monopile head. The relationship between the mobilization coefficient and monopile head rotation is established by back-analyzing test results measured from series of laterally loaded pile tests, and then a general design procedure for a laterally loaded rigid monopile in cohesive soil is recommended. The feasibility and reliability of the proposed design model is validated against three cases of numerical simulations on laterally loaded piles in cohesive soils. It shows that this study’s proposed design model produces a relatively satisfactory prediction of the nonlinear load-deformation response, and can be used for laterally loaded monopile design in the sites with undrained shear strength being uniform or increasing linearly with depth.